2007
DOI: 10.1086/513866
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum Transport and Proton–Alpha‐Particle Differential Streaming in the Solar Wind

Abstract: The interplay between the protonYalpha-particle differential flow speed, v p , and angular momentum transport in the solar wind is explored by using a three-fluid model. The force introduced by the azimuthal components is found to play an important role in the force balance for ions in interplanetary space, bringing the radial flow speeds of protons and alpha particles closer to each other. For the fast solar wind, the model cannot account for the decrease of v p observed by Helios between 0.3 and 1 AU. Howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Due to the bending of the magnetic field lines, however, the azimuthal velocity of the alpha particles changes sign at some point between r eff and r 0 . These results for the azimuthal flow are in agreement with previous studies of angular-momentum transport in the solar wind and show the importance of the differential streaming for the azimuthal-flow components and angular-momentum transport in the solar wind Li et al 2007). Our model, however, extends these previous treatments by including the interplay of micro-instabilities and the rotational force.…”
Section: Zero Heliographic Latitudesupporting
confidence: 92%
See 1 more Smart Citation
“…Due to the bending of the magnetic field lines, however, the azimuthal velocity of the alpha particles changes sign at some point between r eff and r 0 . These results for the azimuthal flow are in agreement with previous studies of angular-momentum transport in the solar wind and show the importance of the differential streaming for the azimuthal-flow components and angular-momentum transport in the solar wind Li et al 2007). Our model, however, extends these previous treatments by including the interplay of micro-instabilities and the rotational force.…”
Section: Zero Heliographic Latitudesupporting
confidence: 92%
“…The rotational force is another collisionless mechanism that reduces the relative drift speed between protons and alpha particles Li et al 2007;McKenzie et al 1979). Roughly speaking, alpha particles and minor ions can be viewed as beads sliding on a wire, where the wire is the spiral interplanetary magnetic field, which is anchored to and rotates with the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…The solar wind rotation influences the differential ion‒ion velocities [ McKenzie et al , ; Hollweg and Isenberg , ]. The azimuthal (transverse) particle velocity components importantly affect the radial momentum transport in the solar wind leading to the relative deceleration between alpha particles and protons [ Li et al , ]; this effect, however, does not seem to account for the observed relative deceleration in the fast solar wind between 0.3 and 1 AU but may be relevant for the Ulysses observations [ Li et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the greatest concerns within the current space science community has been increasingly focused on the Sun‐Earth system, which is intimately linked by the solar wind. The solar wind originates from the chromospheric network [ Xia et al , 2003; Xia , 2003; Xia et al , 2004], according to the measurements of ultraviolet emission and Doppler shifting speed in the inner corona, carries non‐Wentzel‐Kramers‐Brillouin Alfvén Waves in the differential flow of multiple ion species [ Li and Li , 2007, 2008], is very likely driven by an ion cyclotron resonance mechanism via the Kolmogorov turbulent cascade [ Li et al , 2004], and transports the angular momentum from the Sun [ Li and Li , 2006; Li et al , 2007; Li and Li , 2009]. The ubiquitous interplanetary solar wind highly fluctuates, owing to outward emanating disturbances from solar activities.…”
Section: Introductionmentioning
confidence: 99%